2007
DOI: 10.1111/j.1540-6296.2007.00116.x
|View full text |Cite
|
Sign up to set email alerts
|

Stock Market Sensitivity to U.K. Firms' Pension Discounting Assumptions

Abstract: ABS TRACTNew UK pension accounting regulations significantly increase the exposure of the balance sheets of UK firms to volatilities in pension fund valuations. We examine whether the abnormal returns of firms that voluntarily used market based pension discount rates are significantly different from the abnormal returns of industrymatched pair samples of firms that retained traditional cost-based valuation assumptions during the period surrounding the release of the related exposure draft. We also examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…The UK‐based research shows that managers exercise considerable discretion over the ERR assumptions linked to the pension plan and that this has stock market implications. Klumpes and McMeeking (2007) find that the UK stock market responded differentially to firms using high or low ERR rates around the time that the new regulation was introduced and is interest rate sensitive to those firms. Klumpes and Whittington (2003) find that the decision of UK firms' to switch ERR voluntarily, when the choice first became available, is associated with pension characteristics rather than just purely corporate variables.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…The UK‐based research shows that managers exercise considerable discretion over the ERR assumptions linked to the pension plan and that this has stock market implications. Klumpes and McMeeking (2007) find that the UK stock market responded differentially to firms using high or low ERR rates around the time that the new regulation was introduced and is interest rate sensitive to those firms. Klumpes and Whittington (2003) find that the decision of UK firms' to switch ERR voluntarily, when the choice first became available, is associated with pension characteristics rather than just purely corporate variables.…”
Section: Introductionmentioning
confidence: 89%
“…However, accounting differences between these approaches are subtle – in terms of the type of discount rate to be used and the frequency with which it can be updated. These subtleties have implications for the choice of the empirical testing procedure to determine capital market participants' assessment of the value‐relevance of pension assets and liabilities to the sponsoring firm's shareholders (Klumpes and McMeeking, 2007).…”
Section: Institutional and Theoretical Antecedentsmentioning
confidence: 99%
“…Recent studies for the UK market have found that the valuation of pension deficits is subject to the choice of actuarial valuation methods such as discount rates and investment strategies (Klumpes and Whittington, 2003) and the stock market reacts differently to the pension funding status under different accounting assumptions (Klumpes and McMeeking, 2007). Besides share prices, evidence has also been found that investors tend to give different weightings to pension deficits recognised in the balance sheet as opposed to off-balance sheet deficits (disclosed in footnotes) in the 6 determination of other market variables such as corporate bond spreads (Cardinale, 2005).…”
Section: Related Research On the Stock Market Reaction To Pension Defmentioning
confidence: 99%
“…Prior research suggests that in the UK there are persistently large cross-sectional variations in reported ERR assumptions in employers' annual reports (Whittington and McGeachin 2003). There is also evidence suggesting that the UK capital market appears to react differently to pension earnings of firms that frequently adjust their reported ERR assumptions (Klumpes and McMeeking 2007). Furthermore, Klumpes et al (2009) find that UK firms' real economic pension decisions are inter-related with their accounting discretion over reported pension estimates.…”
Section: Introductionmentioning
confidence: 95%